Wachsende Stadt Bremen - Andreas, Verena,Böhme, René,Fortmann, Fabian,Holtermann, Jens,Nischwitz, Guido (Institut Arbeit und Wirtschaft (iaw), Universität, 2018)
Zusammenfassung:
Literaturverzeichnis: Seite 107-110
Keywords: (stw)Stadtwachstum; (stw)Mobilität; (stw)Städtischer Arbeitsmarkt; (stw)Wohnungsmarkt; (stw)Bremen; Graue Literatur; Stadt; Suburbanisierung; Migration; Reurbanisierung; Wachstum; Mobilität; Arbeitsmarkt; Wohnungsmarkt